Platelet Function During Extracorporeal Membrane Oxygenation in Adult Patients - Balle, Camilla Mains; Jeppesen, Anni Nørgaard; Christensen, Steffen; Hvas, Anne-Mette (Frontiers in Cardiovascular Medicine, 2019)
Objective: Hemorrhagic and thromboembolic complications are common during support with extracorporeal membrane oxygenation (ECMO). As platelets play a pivotal role in hemostasis, we aimed to clarify how ECMO support affects platelet function. Methods: We included 33 adult patients undergoing ECMO support at a tertiary ECMO-referral center at Aarhus University Hospital, Denmark. Blood samples were collected on the first morning following ECMO initiation, and subsequently every morning until the 7th (+/-1) day. Platelet aggregation was evaluated by whole blood impedance aggregometry (Multiplate Analyzer) using adenosine diphosphate (ADPtest), arachidonic acid (ASPItest), and thrombin-receptor-agonist-peptide-6 (TRAPtest) as agonists. A new model was applied, taking platelet count into consideration in interpretation of impedance aggregometry analyses. On the 1st and 3rd day, platelet activation was assessed by flow cytometry (Navios) using collagen-related peptide, ADP, TRAP, and arachidonic acid as agonists. Results: Blood samples from all 33 patients were analyzed on day 1 of ECMO support; 24 patients were still receiving ECMO and analyzed on day 3; twelve patients were analyzed on day 7 (+/-1). After ECMO initiation, platelet counts decreased significantly (p < 0.002) and remained low during ECMO support. ECMO patients demonstrated significantly reduced platelet aggregation on day 1 compared with healthy controls (all p-values < 0.001). However, when taking platelet count into consideration, platelet aggregation relative to platelet count did not differ from healthy controls. Flow cytometry analyses demonstrated an impaired platelet activation in ECMO patients on day 1 compared with healthy controls (all p-values < 0.03). No substantial difference was found in platelet activation from day 1 to day 3 on ECMO support. Conclusions: Employing impedance aggregometry and flow cytometry, we found both impaired platelet aggregation and decreased platelet activation on day 1 of ECMO support compared with healthy controls. However, platelet aggregation was not impaired, when interpreted relative to the low platelet counts. Furthermore, levels of bound fibrinogen, on the surface of activated platelets in ECMO patients, were higher than in healthy controls. Together, these findings suggestively oppose that platelets are universally impaired during ECMO support. No marked difference in activation from day 1 to day 3 was seen during ECMO support.